2021
DOI: 10.1590/2179-8087-floram-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release Fertilizer and Container Volume to Produce Inga laurina Seedlings

Abstract: This study evaluated the production of Inga laurina (Sw.) Willd seedlings in 110 and 280 cm 3 tube containers and growing doses (0, 3, 6 and 12 kg m-3) of controlled-release fertilizer (CRF) (15-09-12) and their performance at 5 and 12 months after outplanting. The experiment was conducted using a randomized split-plot design, in a 2 x 4 arrangement (tube volumes x CRF doses). Stabilized sewage sludge from urban origin was used as substrate. It was assessed growth and biomass of the seedlings in nursery, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
5
0
1
Order By: Relevance
“…The effect of the reduction in container volume is closely related to the species (Barbosa et al, 2013) and, mainly, to the period necessary for the production of seedlings (Campany et al, 2017;Cabreira et al, 2021), since seedlings produced in larger containers may show better vegetative performance after transplantation, as observed in Inga laurina (Cabreira et al, 2021). However, the effect of container volume is tied to other factors such as irrigation frequency (Ouma, 2007;Espinoza et al, 2017;Silva et al, 2018a, b;Nascimento Neto et al, 2020), as observed in the present study, with more negative effects of the reduction in container volume on the growth of T.…”
Section: Effects Of Container Volumementioning
confidence: 99%
“…The effect of the reduction in container volume is closely related to the species (Barbosa et al, 2013) and, mainly, to the period necessary for the production of seedlings (Campany et al, 2017;Cabreira et al, 2021), since seedlings produced in larger containers may show better vegetative performance after transplantation, as observed in Inga laurina (Cabreira et al, 2021). However, the effect of container volume is tied to other factors such as irrigation frequency (Ouma, 2007;Espinoza et al, 2017;Silva et al, 2018a, b;Nascimento Neto et al, 2020), as observed in the present study, with more negative effects of the reduction in container volume on the growth of T.…”
Section: Effects Of Container Volumementioning
confidence: 99%
“…In fact, the root system is so crucial that several studies have pointed out that regardless of the species evaluated, RDB is the variable that most influences the other variables and DQI, constituting the leading indicator of seedling quality (Rossa et al 2013, Grossnickle andEl-Kassaby 2016). Other research has also frequently found that although seedlings produced in larger packages have significantly higher heights in the nursery, this difference dissipates within a few months after planting, and seedling growth mainly depends on the quality of the root system (Feletti et al 2020, Cabreira et al 2021. With well-formed root systems, seedlings more efficiently absorb the nutrients made available during planting, and smaller seedlings gradually reach the larger seedlings.…”
Section: Containersmentioning
confidence: 99%
“…Many containers are used to produce native species seedlings, from traditional "plastic bags" to biodegradable materials, with rigid plastic tubes being the most commonly used material. The wide use of these tubes has been justified by lower substrate consumption and optimization of time and production area and the ease of field transport and good root system formation (Cabreira et al 2021). In contrast, the need to disinfect packaging, high shipping costs and damage to the root system have required viable alternatives to this production system.…”
Section: Introductionmentioning
confidence: 99%
“…Solid waste from sewage treatment is known as sewage sludge (SS) and has been tested and approved as a substrate for seedling production of forest species 7 , 8 . This material is being used in the Rio de Janeiro State Water and Sewage Company (CEDAE) nurseries, which produced more than 1,000,000 seedlings between 2015 and 2019 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of SS in the substrate for producing Schinus terebinthifolia seedlings can be considered viable or even beneficial, having been evaluated by Nóbrega et al (2007) 17 , Trigueiro and Guerrini (2014) 18 , Abreu et al (2018) 19 , among other authors. In addition, other studies have evaluated substrates containing SS compared to CSs 20 22 or the effects of chemical fertilizers 7 , 16 , 23 in forest seedlings production. However, the evaluation of different substrates combined with CRF rates is little studied for Atlantic Forest species, especially when considering a substrate containing 100% SS, as evaluated in the present study.…”
Section: Introductionmentioning
confidence: 99%